Double trouble: Time-varying connectedness between stock and housing markets - Guo, Kaiyi; Chiang, Shu-hen; Lee, Hsin-Jung; Chen, Chien-Fu (International Journal of Strategic Property Management, 2025)
Joint new records in the stock and housing markets are now gradually becoming a focal point of controversy in Taiwan. Based on the local heterogeneity of real estate assets, this study proposes setting up a two-market transmission mechanism between the stock and city-level housing markets to fully reply to this question. The estimation results using the Diebold-Yilmaz spillover method offer some critical information: the fact that the overheated housing market is precisely caused by the Taiwan stock market, which serves as evidence of the wealth effect. As far as the housing network is concerned, it is interesting to note that housing prices in Taipei as the source city spill out from near to far: New Taipei, Taichung and ultimately Kaohsiung. All these things make it clear that the authorities pay special attention to the status of the stock market as well as to inter-city differences in terms of housing spillovers.